Performance analysis on an integrated three-area thermal AGC system with various wind velocities considering HCSA-optimized PI-TIDN Controller - Naladi Ram Babu; Tirumalasetty Chiranjeevi; Ramesh Devarapalli; Fausto Pedro García Márquez (Archives of Control Sciences)
This article investigates the impact of a high-voltage direct-current (HVDC) link and a wind turbine system (WTS) on the dynamics of a three-area thermal automatic generation control (AGC) system. A novel controller, the cascade of proportional-integral (PI) and tiltintegralderivative (TID) with filter coefficient (N) (PI-TIDN) controller is projected. The WTS units are subjected to various wind velocity scenarios, including fixed and random wind velocities. The controller parameters are concurrently enhanced using the hybrid crowsearch algorithm (HCSA). The system dynamics corresponding to the PI-TIDN controller are superior to those of PIDN and TIDN controllers. Additionally, studies with different wind velocities demonstrate that responses with fixed wind velocities are better than those with random wind velocities. Moreover, integrating WTS units with the thermal system improves dynamics compared to the thermal system alone. It is also apparent that the parallel AC-HVDC system enhances dynamics. Furthermore, sensitivity analysis exposes that the PI-TIDN controller values at nominal settings are vigorous and do not require retuning.